Reply to Evteev and Heuzé: How to overcome the problem of modeling respiration departing from bony structures - de Azevedo, Soledad (2018)
"Reply to Evteev and Heuzé: How to overcome the problem of modeling respiration departing from bony structures" is a reply to a letter from Andrej A. Evteev and Yann Heuzé: "Impact of sampling strategies and reconstruction protocols in nasal airflow simulations in fossil hominins", which is related to a previous paper "Nasal airflow simulations suggest convergent adaptation in Neanderthals and modern humans".